Silicon induces resistance to Diatraea saccharalis in sugarcane and it is compatible with the biological control agent Cotesia flavipes - Santos-Cividanes, Terezinha M.; Cividanes, Francisco J.; Garcia, Júlio C.; Vilela, Michelle; Moraes, Jair C.; Barbosa, José Carlos [UNESP] (Springer Nature, 2022)
The sugarcane borer Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae) is a major pest of sugarcane (Saccharum sp.) (Glumiflorae: Poaceae) in Brazil and has been controlled efficiently with the parasitoid Cotesia flavipes (Cameron) (Hymenoptera: Braconidae). Addition of a silicon source to the soil induces resistance to insect pests in the host plant and can be integrated with other pest-management tactics such as biological control. This study evaluated the effects of silicon on the tritrophic interactions among sugarcane, D. saccharalis, and its natural enemy C. flavipes. Sugarcane varieties (one resistant and one susceptible to the sugarcane borer) cultivated with or without silicon constituted the four treatments. IACSP 96–2042 (susceptible variety) benefited from silicate addition as the length of tunnels bored by D. saccharalis was reduced by 43%. Tunnel length in the resistant variety (IACSP 96–3060) did not change with silicon application. The fresh mass and larval body size of the sugarcane borer were not affected by the treatments. Parasitism by C. flavipes on the sugarcane borer and the morphometric parameters of this parasitoid were not affected by silicon addition, nor were cane yield and quality parameters of the two sugarcane varieties. Treatment with silicon in the management of D. saccharalis was compatible with the parasitoid C. flavipes. This study constitutes the first field evaluation of the performance of C. flavipes combined with the effect of silicon as a resistance factor in D. saccharalis control in sugarcane.
Keywords: Biological control; Calcium silicate; Parasitoid; Saccharum sp